2021
DOI: 10.3389/fpsyt.2021.678891
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Biases in Blood-Injection-Injury Phobia: A Review

Abstract: Blood-injection-injury (BII) phobia can lead to avoidance of crucial medical procedures and to detrimental health consequences, even among health workers. Yet unlike other specific phobias, BII phobia has been understudied. Specifically, while cognitive biases have been extensively investigated in other anxiety disorders, little is known about the same biases in BII phobia. The current article reviews cognitive biases in BII phobia and suggest future directions for further study and treatment. The reviewed bia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 85 publications
(97 reference statements)
1
6
0
Order By: Relevance
“…These results are in line with previous studies showing a similar gender and age effect 2,50-52 as well as the fact that females compared to males are more likely to be diagnosed with SP 53,54 . This is also in line with the results of past studies 1,16,20,21,23,25,55 and suggests the notion that there are shared factors across SP subtypes. The fact that the prevalence and intensity of most phobias tend to decrease with age 56 and that females are at higher risk of developing an SP is well-established 57 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are in line with previous studies showing a similar gender and age effect 2,50-52 as well as the fact that females compared to males are more likely to be diagnosed with SP 53,54 . This is also in line with the results of past studies 1,16,20,21,23,25,55 and suggests the notion that there are shared factors across SP subtypes. The fact that the prevalence and intensity of most phobias tend to decrease with age 56 and that females are at higher risk of developing an SP is well-established 57 .…”
Section: Discussionsupporting
confidence: 91%
“…We also wanted to investigate the unique pattern of risk factors associated with SPs, as there is great variability in prevalence 2 , stimulus element triggering fear 28 , the likelihood of impairment, comorbidity, and personality problems 17 , cognitive ER strategies 25 and brain activation pattern 23,29,30 of SP subtypes. As expected, our results clearly show that each SP subtype has a different pattern of associated factors; further, some factors only appear for one subtype and not for the others.…”
Section: Discussionmentioning
confidence: 99%
“…Needles are routinely used in various clinical settings [ 1 ] to enable the delivery of drugs, vaccines, and other substances into the body or for fluid and tissue extraction, [ 2 ] and billions of injections are administered annually worldwide according to the WHO [ 3 ]. Needle phobia is an understudied condition, [ 4 ] which is experienced by patients undergoing procedures such as venipunctures and blood donations as well as those with chronic conditions necessitating frequent injections [ 5 – 8 ]. Needle fear exists on a continuum of severity, and can lead to delayed therapy, treatment avoidance, and vaccine hesitancy [ 6 , 7 , 9 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, using maladaptive ER strategies more often was linked to a heightened level of animal-, BII-related fears, and social anxiety 10,13,14 . However, a recent study 21 showed that the pattern of ER strategies used differs by the subtype of phobia, possibly because of a difference in the neurocognitive mechanisms underlying the subtypes [22][23][24][25] . Thus, our second aim was to discover the pattern of the strategies involved in the three subtypes of fears (animal-, BII phobia, and social anxiety) with the highest lifetime prevalence.…”
Section: Discussionmentioning
confidence: 99%